2012
DOI: 10.1371/journal.pone.0037587
|View full text |Cite
|
Sign up to set email alerts
|

A2 Noradrenergic Lesions Prevent Renal Sympathoinhibition Induced by Hypernatremia in Rats

Abstract: Renal vasodilation and sympathoinhibition are recognized responses induced by hypernatremia, but the central neural pathways underlying such responses are not yet entirely understood. Several findings suggest that A2 noradrenergic neurons, which are found in the nucleus of the solitary tract (NTS), play a role in the pathways that contribute to body fluid homeostasis and cardiovascular regulation. The purpose of this study was to determine the effects of selective lesions of A2 neurons on the renal vasodilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 46 publications
6
20
1
Order By: Relevance
“…Similar to the resultsthat were obtained in the present study, HS infusion caused hypertension in intact rats [10], [16], [49], [59], [60]. The pressor responses appeared to be due to an increase in lumbar sympathetic nerve activity and vasopressin release [10], [59], [60].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the resultsthat were obtained in the present study, HS infusion caused hypertension in intact rats [10], [16], [49], [59], [60]. The pressor responses appeared to be due to an increase in lumbar sympathetic nerve activity and vasopressin release [10], [59], [60].…”
Section: Discussionsupporting
confidence: 90%
“…Previous reports support the assertion that a loss in immunoreactivity is indicative of neuronal death [17], [49], [50]. The mechanism of specific internalization of anti-D β H–saporin implies that only cells synthesizing D β H can take up the conjugated toxin.…”
Section: Discussionmentioning
confidence: 59%
“…1B). In addition, the A2 noradrenergic neurons in the NTS that are activated by cardiopulmonary receptors also project to the PVN, indicating that a catecholaminergic projection could also be a transmitter candidate (Appleyard et al 2007;Pedrino et al 2012). Thus, in terms of reflex control of cardiovascular regulation, we are now in a position to link the sensory inputs to the NTS with specific neuronal…”
Section: Afferent Projections To the Pvnmentioning
confidence: 99%
“…; Pedrino et al . ). Thus, in terms of reflex control of cardiovascular regulation, we are now in a position to link the sensory inputs to the NTS with specific neuronal targets in the PVN that regulate sympathetic activity either directly or indirectly.…”
Section: Introductionmentioning
confidence: 97%
“…A possible action on the carotid bodies is suggested by the finding that sinoaortic denervation attenuated the recovery of MAP in response to hypertonic saline (8). In addition, recent studies have also suggested a role for A2 noradrenergic neurons since the decrease in RSNA in anesthetized rats following hypertonic saline infusion is abolished with lesion of these neurons (35).…”
Section: R570mentioning
confidence: 99%